Generation of chemical deposits on fused silica optics and their modulation on the light intensity distribution - Ye, Hui; Cui, Zhuangzhuang; Li, Zhuang; Yang, Wei; Qian, Yuan (Applied optics. Optical technology and biomedical optics, 2022)
Deposited substances generated from hydrofluoric acid based (HF-based) etching are found to be the precursors that deteriorate the resistance of fused silica optics to laser damage. In this paper, the surface of polished fused silica was treated with a buffer oxide etchant (BOE, 5-10%wt. HF + 10%wt. +80-85 . ). The optic surface area affected by the etching-induced deposits ( ) was found to increase significantly with the amount of material removal and sensitivity to the post-cleaning procedure. Three shapes of deposited particles are simultaneously identified on the treated samples. The 3D finite-difference time-domain (FDTD) was used to simulate the light field distribution near the deposited particles, which demonstrates that fused silica is subject to more light modulation when a particle is exposed on the front surface laser than on the rear surface laser. In addition, dense particles barely increase the light intensification factor (LIF) while markedly increase the light focused probability inside fused silica. Moreover, a multiple linear regression (MLR) analysis for the LIF builds a fitting plane model of the LIF and the particle height as well as the horizontal size, revealing that the LIF increases with the size of the deposited particle, especially its height. The laser damage testing results indicate that a deposited layer of  ∼76 in height had little influence on the laser-induced damage threshold (LIDT) of the optics and larger deposited particles with up to 9 µm thickness may deteriorate the LIDT to 41.62% that of the reference sample. Both the simulation and experimental results demonstrate that deposited particles with a height of more than 0.1 µm should be inhibited to achieve fused silica with superior laser damage performance.